1969
DOI: 10.1002/bip.1969.360080408
|View full text |Cite
|
Sign up to set email alerts
|

Chain conformation of copoly(γ‐methyl D, L‐glutamate)

Abstract: SynopsisCopolymers of 7-methyl D-and L-glutamates with various D/L ratios were prepared. Infrared absorption spectra of solid films were measured and sums of right-and lefthanded helix contents were determined from intensities of amide V bands. Farultraviolet absorption spectra and optical rotatory dispersion of these copolymers ill solutions are used to ascertain their helical character. Chain conformations of DLcopolypeptides are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1970
1970
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…In this work, we discuss the preparation, structure, and surface characteristics of A-B-A tri-block copolymers consisting of DL-isomers of poly(ymethyl glutamate) as the A component and polybutadiene as the B component. Conformation studies ofpoly(y-methyl D,L-glutamate) have been made by et al 15 and Nakajima et af.1 6 and show that the helical content in the membranes steadily decreases from 100% to 80% as the fraction of the Dresidue is increased from 0 to 50%. Furthermore, these authors found that the helical content of the right-handed a-helical form for poly(y-methyl D,Lglutamate) in which D-residue is 50% equals the helical content of the left-handed form.…”
mentioning
confidence: 99%
“…In this work, we discuss the preparation, structure, and surface characteristics of A-B-A tri-block copolymers consisting of DL-isomers of poly(ymethyl glutamate) as the A component and polybutadiene as the B component. Conformation studies ofpoly(y-methyl D,L-glutamate) have been made by et al 15 and Nakajima et af.1 6 and show that the helical content in the membranes steadily decreases from 100% to 80% as the fraction of the Dresidue is increased from 0 to 50%. Furthermore, these authors found that the helical content of the right-handed a-helical form for poly(y-methyl D,Lglutamate) in which D-residue is 50% equals the helical content of the left-handed form.…”
mentioning
confidence: 99%
“…29 We adopted b 0 , h = -600 for PMLG in m-cresol and -615 for PBLG in DMF, respectively, and b0, c = 0 for both cases. 30 Masuda et a/., 24 have pointed out that the IR method is useful for estimating the helix content of solid polypeptide samples, and proposed that the IR peak intensity of the amide Polymer J., Vol. 16, No.…”
Section: Chain Conformation Ofdl-copolypeptidesmentioning
confidence: 99%
“…In Figure 2, the amide V band of the a-helix was observed at 615 cm-1 for PMLG and PMDG, while thatfor PMDLG was at 620-630cm-1 • Masuda, et al, 4 proposed to estimate the helix content from the peak intensity of the amide V band relative to that at 2950 cm -i, and calculated the helix content of PMDLG from their experimental data.…”
Section: Infrared Absorption Measurementsmentioning
confidence: 99%
“…According to Wada 2 , helices characterized by a unique helical sence are maintained even for o, L-copolymer containing up to about 25-% minor component. This means that minor n-residues(L-residues) may be incorporated in right-handed(left-handed) helix mainly composed of major L-residue(n-residues).More recently, Masuda, et al,4 published results on o, L-copoly(r-methyl glutamate) (PMDLG), polymerized with sodium methoxide as the initiator and dioxane as the solvent, and pointed out that the formation of the left-handed helix is appreciable even at low n-residue content.In the present study, PMDLG covering the whole range of o, L compositions was synthesized 10 …”
mentioning
confidence: 99%
See 1 more Smart Citation